2004
DOI: 10.1002/pits.10166
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the criterion validity and sensitivity to brief intervention of alternate curriculum‐based measures of writing skill

Abstract: Curriculum-based measures have been validated for use in evaluating reading, mathematics, and writing skills (Marston, 1989). Despite its common use by school psychologists (Wilson & Reschly, 1996), the relationship between the Woodcock Johnson-Revised and curriculum-based measures of writing has not been evaluated. This study investigated the relationship between the Woodcock Johnson-Revised Writing Samples subtest and alternate curriculum-based measures of written expression. In addition, the sensitivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 16 publications
2
27
1
Order By: Relevance
“…Additionally the children's productivity in terms of amount of words produced aligns with those reported in other studies for similar age groups (McMaster & Espin, 2007). As with previous research we found total number of words written and CWS discriminated between year groups (Gansle et al, 2002;Gansle et al, 2006;McMaster & Espin, 2007;Weissenburger & Espin, 2005). Few studies have considered punctuation marks and, although they were relatively infrequent in the pupils written texts, number of punctuation marks also discriminated between year groups (Gansle et al, 2006).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Additionally the children's productivity in terms of amount of words produced aligns with those reported in other studies for similar age groups (McMaster & Espin, 2007). As with previous research we found total number of words written and CWS discriminated between year groups (Gansle et al, 2002;Gansle et al, 2006;McMaster & Espin, 2007;Weissenburger & Espin, 2005). Few studies have considered punctuation marks and, although they were relatively infrequent in the pupils written texts, number of punctuation marks also discriminated between year groups (Gansle et al, 2006).…”
Section: Discussionsupporting
confidence: 69%
“…These assessments involve pupils writing for short periods (between three and seven minutes) in response to a probe and have been shown to be valid and reliable measures of writing proficiency for students aged between seven and 12 (Weissenburger & Espin, 2005 of CWS and measures of spelling may also provide more face validity for teachers (Coker & Ritchey, 2010;Gansle, Noell, VanDerHeyden, Naquin, & Slider, 2002).…”
Section: Curriculum Based Measures Of Writingmentioning
confidence: 99%
“…The production-dependent indicators are the most similar to other CBM outcome measures in that they are largely rate-based and sensitive to instruction-related growth (Gansle et al, 2004), yet appear to have declining criterionrelated validity as grade level increases (see McMaster & Espin, 2007). Compared with the production-dependent indicators, the produc tion-independent indicators have higher validity coefficients, more so as grade level increases (Jewell & Malecki, 2005;Tindal & Parker, 1989; see also McMaster & Espin, 2007 for review).…”
Section: Written Expression Curriculum-based Measuresmentioning
confidence: 97%
“…In fact, Kristen A. Gansle et al (2004) called attention to the promising subfield of punctuation in writing research, stating that since punctuation is an easily measurable element of language, it is worthwhile to explore whether there is a correlation between writing ability and punctuation usage. For students learning how to write in their native language, evidence for a possible correlation was found between quality of writing and mastery of the English punctuation system; this area of writing seems especially beneficial to teachers who wish to help advanced students who lack this ability in writing.…”
Section: Punctuationmentioning
confidence: 98%